Potential of production bioplastic from potato starch - Hamidon, Nuramidah; Hamidun, Mariana; Arish, Nur Aini; Sunar, N.M.; Ali, R.; Hamid, H. A.; Harun, H.; Muhamad, Mimi Suliza (Penerbit Uthm, 2018)
Plastic waste is a global issue, rapidly escalating, with approximately 311 million tons of plastic produced world- wide in 2014 [29]. The development of the chemical process for manufacturing synthetic polymers which is plastics made of crude oil and petroleum was a breakthrough of chemistry and in material sciences and it paved the way to the production of one of the most versatile group of materials ever produced. These synthetic polymers combined features exhibiting strength, flexibility, light weight and easy and low cost production. However, found to be extremely durable and were considered among the most non-biodegradable synthetic materials [26]. The major disposal method of these materials is incinerated or landfilled, which both are not sustainable and not environmentally friendly solutions [22]. Plastics are widely used in almost all industries, especially in the packaging and building sectors, due to their great versatility, low weight and excellent electrical and thermal insulation properties [3]. From the environmentally friendly point of view, the production of biodegradable plastics is important to reduce the pollution of plastic waste in the environment compare to degradable plastics. Petroleum-based plastic products are characterized as not easily degradable compare to starch based as the degradable additives [26]. There is a study that published in Science, they estimated that out of 192 coastal countries in the world, Malaysia at the eight largest producer of mismanaged plastic wastes. They also estimated in 2010, Malaysia had produced around 0.94 million of tons mismanaged plastic wastes, which is 0.14 to 0.37 million tons may have been washed into ocean [28].